Evaluation of the frequency/addiction of smartphone use and its effect on sleep quality in university students (Annals of Medical Research, 2021)
Aim: In the last century, the use of technological devices has increased rapidly, and smartphones have managed to enter the list of products used by almost everyone because of their various features. Technology addiction, which is the result of misuse or overuse of technology, has entered into the literature in this period and has biological, psychological, and sociological effects. Smartphone addiction is considered as a problem that can affect the youth in university as well as all age groups in every aspect of health. In this study, we aimed to measure the effect of smartphone addiction on sleep quality, which affects the individual’s biopsychosocial life.Material and Methods: The study consists of students of the University of Health Sciences, Hamidiye Vocational School of Health Services. The sample group consisted of 161 students selected by the simple randomization method. A questionnaire was used as a data collection tool, Smartphone Addiction Scale - Short Version, Pittsburgh Sleep Quality Index, and the data were analyzed with the SPSS 22.0 Program.Results: According to the findings of the study, all students use smartphones. The smartphone addiction rate was 31.1%, and reduced sleep quality rate was 47.8% among students. There was a significant relationship between smartphone addiction and sleep quality.Conclusion: In our study, considering the importance of quality sleep in terms of biopsychosocial health of the individual, the importance of raising the awareness of young people to use the technology correctly and as necessary was demonstrated.
Keywords: Addiction; sleep hygiene; health occupations students; preventive medicine